MODEL APPLICATION OF IMPROVING SKILL LEARNING PAIKEM GEMBROT FOR ESSAY WRITING DESCRIPTION CLASS V SD STATE 184 PEKANBARU - Pratama, Fauzan Pratama Fauzan; Kurniaman, Otang Kurniaman Otang; Marhadi, Hendri Marhadi Hendri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstrak : This research is motivated by the lack of a description of the student write a essay skills. It can be seen from the average value obtained students' writing skills in write a essay descriptive material is 63.50. Subjects in this study were students of class V SD Negeri 184 Pekanbaru. The method used is a classroom action research that will be conducted in two cycles. Based on the research results, the average value of the initial score essay writing skills of students is 63.25 to 45.00 % classical completeness In the first cycle class average value increased to 71.19, up 7.94 units of initial data with classical completeness percentage reached 62.50 %. Then the average value of the class on the second cycle into 80.24, an increase of 16.99 units classical completeness of the initial data has reached 90.00 %. Improved skills of essay writing is supported by : The average percentage of 71.43 % of teachers activity in both categories . In the second cycle the average activity of 83.93 % teachers with very good category, the increase in the average activity of the teacher of the first cycle to the second cycle of 12.5 points (17.5 %). The average percentage of student activities at 66.07 with both categories. In the second cycle average of 82.14% of student activity with excellent category, an average increase student activity from the first cycle to cycle II of 16.07 points (24.32 %). Based on the translation of the above it can be concluded that by applying the learning model PAIKEM fat can improve essay writing skills graders State V SD 184 Pekanbaru .Keyword : Paikem Gembrot, Essay Description